Wage rate and employment in the manufacturing sector of Malaysia - Yusoff, Mohammed (2013)
This paper examines the importance of Malaysian manufacturing industries to the domestic economy and then estimates the demand for labor as a function of wage rate, output, and capital. The study uses the survey data of firms categorized according to the 3-digit Malaysian Standard Industrial Classification. The manufacturing sector has been contributing significantly to the Malaysia’s economy in terms of its contribution to GDP, employment, and exports. The OLS results suggest that wage rate, output or production, and capital are all important determinants of labor employment in the manufacturing sector in Malaysia. Although their elasticities with respect to employment of labor are all inelastic, the demand for labor is relative more responsive to the changes in the output and capital than the wage rate. Therefore implementing policies to encourage capital accumulation and overall economic growth are indeed helpful to boost employment in the manufacturing sector. Malaysia’s manufacturing output are mostly exported to foreign countries. This study indicates that the wage rate is an important determinant of labor demand in the manufacturing sector. Malaysia therefore has to manage it wage structure carefully such that the increase in wage rate must be in line with the increase in labor productivity. Otherwise Malaysian exports of manufactures will not be competitive in the world market and this will adversely affect the performance of Malaysian economy since Malaysia has been an export-oriented country in which exports have been the engine of growth.